LEVEL OF EDUCATION AS A FACTOR URBAN DEVELOPMENT TO MINIMIZE NEGATIVE EFFECT FOR IMPLEMENTATION OF INVESTMENT AND CONSTRUCTION PROJECTS (Municipal economy of cities (Technical science), 2013)
Some issues to overcome negative trends in urban planning and architecture and ways to minimize the negative impact by raising the cultural level implementation of urban development.